Expression of immune‐related genes in rectum and colon descendens of Irritable Bowel Syndrome patients is unrelated to clinical symptoms. Issue 6 (10th March 2019) - Aguilera‐Lizarraga, Javier; Florens, Morgane V.; Van Brussel, Thomas; Clevers, Egbert; Van Oudenhove, Lukas; Lambrechts, Diether; Wouters, Mira M.; Boeckxstaens, Guy E.
Abstract: Background: Mucosal immune activation has been postulated to play an important role in the pathogenesis of irritable bowel syndrome (IBS). However, data are conflicting and often based on small patient cohorts. Here, we aimed to evaluate the gene expression of a large set of immune‐related genes in mucosal biopsies from IBS patients and healthy volunteers (HV). Methods: A total of 171 IBS patients and 127 HV were included in the study. Rectum biopsies were collected from a cohort of 70 HV and 77 IBS patients (Rome III) and colon descendens biopsies from another cohort of 57 HV and 94 IBS patients (Rome II). Gene expression was assessed using OpenArray technology, and validated questionnaires were used to evaluate clinical characteristics (GI symptoms, somatization, anxiety, and depression). Key Results: A subset of IBS patients (33%) with increased immune activation in the colon descendens was identified using multivariate analysis and displayed increased gene expression of IL1B (3‐fold change), prostaglandin synthase PTGS2 (2.1‐fold change), and the G‐protein‐coupled receptor MRGPRX2 (10.7‐fold change). Clinical characteristics in this subgroup were however similar to the rest of the patient cohort. Analysis of rectal biopsies failed to identify such subgroup of "immuno‐active" IBS patients in the other patient cohort. Conclusion: A subset of IBS patients reveals evidence of immune activation in the colon descendens, but not in the rectum; however, gene expression is unrelated to clinical symptoms. To what extent this subgroup might however respond to anti‐inflammatory therapy remains to be investigated. Abstract : The role of low‐grade inflammation and mucosal immune activation in irritable bowel syndrome (IBS) is controversial and remains poorly understood. We used multivariate analysis of the mucosal gene expression to identify a subset of patients with evidence of increased immune activation in the colon descendens, but not in the rectum. However, the clinical characteristics of the immuno‐active subgroup did not differ from the rest of the IBS patient cohort, therefore suggesting no direct relationship between mucosal low‐grade inflammation and symptoms in IBS.